AstraZeneca – The Success Links Back To Organization - Alajmi, Rakan; Albaseri, Shaikha; Alawadhi, Rawan; Alhabashi, Hala (Journal of The Community Development in Asia, 2023)
AstraZeneca is a globally leading patient focused pharmaceutical company that targets to address diseases across Oncology, BioPharmaceuticals, and Rare Disease. While that many have come to know of it in the recent years for its fight against COVID-19, the company has been known for various achievements and innovation in saving human life. It has in place a straightforward strategy that becomes a key factor of its success and the main aim of this research paper. The strategy connects business growth with the needs of human life and the limitations and possibilities on Earth. AstraZeneca’s strategy revolves around advancing in producing disruptive biology through modern technology of AI and Data Science, delivering business growth and having an impact on society through brilliant leadership, and most importantly being a great place to work.How are these areas being worked on to allow AstraZeneca to become a leader in the health industry that aims to save human beings from harmful diseases? It clearly links back to its strategy and the organization design that is not stopping innovation at any cost Keywords – organization strategy, innovation, leadership, healthcare, organization design, modern technology.